Just when you thought things couldn't get worse the cartoons and comic strips of Edward Sorel - Sorel, Edward 1929- (Fantagraphics Books, 2007)
Collects the best comics from over 30 years of work by artist Edward Sorel
Keywords: American wit and humor, Pictorial; Caricatures and cartoons -- United States; Humoristische Darstellung; USA; Comic; Karikatur